The immunomodulatory potential of natural compounds in tumor-bearing mice and humans. Issue 6 (26th March 2019) - Pan, Pan; Huang, Yi-Wen; Oshima, Kiyoko; Yearsley, Martha; Zhang, Jianying; Arnold, Mark; Yu, Jianhua; Wang, Li-Shu
Abstract: Cancer is considered a fetal disease caused by uncontrolled proliferation and progression of abnormal cells. The most efficient cancer therapies suppress tumor growth, prevent progression and metastasis, and are minimally toxic to normal cells. Natural compounds have shown a variety of chemo-protective effects alone or in combination with standard cancer therapies. Along with better understanding of the dynamic interactions between our immune system and cancer development, nutritional immunology—the use of natural compounds as immunomodulators in cancer patients—has begun to emerge. Cancer cells evolve strategies that target many aspects of the immune system to escape or even edit immune surveillance. Therefore, the immunesuppressive tumor microenvironment is a major obstacle in the development of cancer therapies. Because interaction between the tumor microenvironment and the immune system is a complex topic, this review focuses mainly on human clinical trials and animal studies, and it highlights specific immune cells and their cytokines that have been modulated by natural compounds, including carotenoids, curcumin, resveratrol, EGCG, and β-glucans. These natural compounds have shown promising immune-modulating effects, such as inhibiting myeloid-derived suppressor cells and enhancing natural killer and cytolytic T cells, in tumor-bearing animal models, but their efficacy in cancer patients remains to be determined.